Influence of Cannabinoid Receptor Deficiency on Parameters Involved in Blood Glucose Regulation in Mice - Zibolka, Juliane (Int J Mol Sci, 2020)
Cannabinoids are known to influence hormone secretion of pancreatic islets via G protein-coupled cannabinoid receptor type 1 and 2 (CB(1) and CB(2)). The present study was designed to further investigate the impact of cannabinoid receptors on the parameters involved in insulin secretion and blood glucose recognition. To this end, CB(1) and CB(2) receptor knockout mice (10–12 week old, both sexes) were characterised at basal state and compared to wild-type mice. The elimination of cannabinoid receptor signalling resulted in alterations of blood glucose concentrations, body weights and insulin levels. Changes were dependent on the deleted receptor type and on the sex. Analyses at mRNA and protein levels provided evidence for the impact of cannabinoid receptor deficiency on the glucose sensing apparatus in the pancreas. Both receptor knockout mouse lines showed decreased mRNA and protein amounts of glucose transporters Glut1 and Glut2, combined with alterations in immunostaining. In addition, pancreatic glucokinase expression was elevated and immunohistochemical labelling was modified in the pancreatic islets. Taken together, CB(1) and CB(2) signalling pathways seem to influence glucose sensing in β-cells by affecting glucose transporters and glucokinase. These alterations were more pronounced in CB(2) knockout mice, resulting in higher blood glucose and lower plasma insulin levels.